Prediction of designer drugs: synthesis and spectroscopic analysis of synthetic cannabinoid analogues of 1H‐indol‐3‐yl(2, 2, 3, 3‐tetramethylcyclopropyl)methanone and 1H‐indol‐3‐yl(adamantan‐1‐yl)methanone. Issue 10 (3rd November 2015) - Carlsson, Andreas; Lindberg, Sandra; Wu, Xiongyu; Dunne, Simon; Josefsson, Martin; Åstot, Crister; Dahlén, Johan
Abstract : In this work, emergence patterns of synthetic cannabinoids were utilized in an attempt to predict those that may appear on the drug market in the future. Based on this information, two base structures of the synthetic cannabinoid analogues – (1 H ‐indol‐3‐yl(2, 2, 3, 3‐tetramethylcyclopropyl)methanone and 1 H ‐indol‐3‐yl(adamantan‐1‐yl)methanone) – together with three substituents – butyl, 4‐fluorobutyl and ethyl tetrahydropyran – were selected for synthesis. This resulted in a total of six synthetic cannabinoid analogues that to the authors' knowledge have not yet appeared on the drug market. Spectroscopic data, including nuclear magnetic resonance (NMR), mass spectrometry (MS), and Fourier transform infrared (FTIR) spectroscopy (solid and gas phase), are presented for the synthesized analogues and some additional related cannabinoids. In this context, the suitability of the employed techniques for the identification of unknowns is discussed and the use of GC‐FTIR as a secondary complementary technique to GC‐MS is addressed. Examples of compounds that are difficult to differentiate by their mass spectra, but can be distinguished based upon their gas phase FTIR spectra are presented. Conversely, structural homologues where mass spectra are more powerful than gas phase FTIR spectra for unambiguous assignments are also exemplified. This work further emphasizes that a combination of several techniques is the key to success in structural elucidations. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Emergence pattern based synthesis of some synthetic cannabinoids and their GC‐MS, GC‐FTIR, FTIR, NMR and ESI‐QTOF‐MS data.